KREATIFITAS DALAM PEMBELAJARAN PAI: STRATEGI KOOPERATIF BERBASIS MIND MAPPING UNTUK MENINGKATKAN KONSENTRASI SISWA - Widia Apriliani; Irma Soraya; Mohammad Kurjum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mind Mapping is a learning approach that is suitable to be applied at the elementary school level because it is in line with the characteristics of students who like active and enjoyable learning activities. In Islamic Religious Education (PAI) subjects, Mind Mapping-based cooperative strategies play a role in increasing students' focus and concentration in learning. This study aims to analyze cooperative strategies in increasing students' concentration at SD TAQUMA Surabaya. The method used is a qualitative approach through literature review with data collection techniques in the form of observation, interviews, and documentation. The findings show that application of Mind Mapping-based cooperative strategies in PAI learning can increase student involvement actively, while fostering values of cooperation, solidarity, and responsibility in groups. The subjects of study were students of SD TAQUMA Surabaya. This approach also has a positive impact on learning motivation, because students feel more involved and active in the learning process. Overall, this strategy not only strengthens students' understanding of religious material but also contributes to the formation of religious characters, noble morals, and is able to apply religious values in everyday life.